2000
DOI: 10.1016/s0014-5793(00)02158-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced epinephrine‐induced platelet aggregation in individuals carrying the G protein β3 subunit 825T allele

Abstract: The 825T allele of a common C825T polymorphism in the gene encoding the L L3 subunit of heterotrimeric G proteins is associated with enhanced activation of pertussis toxin (PTX)-sensitive G proteins. We investigated responses of human platelets upon stimulation with epinephrine, which activates PTX-sensitive G proteins, and with agonists which activate additionally, or exclusively PTX-insensitive pathways. Slopes and maximum of the secondary aggregation were significantly enhanced in platelets from 825T allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…3 Furthermore, G-protein activation is increased to a similar extent, 3 and the associated cellular phenotypes, like chemotaxis, 22 agonist-induced vasoconstriction, 23,24 and epinephrineinduced platelet aggregation, 25 are virtually identical in cells with TC or TT genotype but increased in comparison with those with CC genotype. For these reasons and because the TT genotype is relatively rare in white populations, in previous studies patients homozygous or heterozygous (TT and TC genotypes, respectively) were combined for analysis.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…3 Furthermore, G-protein activation is increased to a similar extent, 3 and the associated cellular phenotypes, like chemotaxis, 22 agonist-induced vasoconstriction, 23,24 and epinephrineinduced platelet aggregation, 25 are virtually identical in cells with TC or TT genotype but increased in comparison with those with CC genotype. For these reasons and because the TT genotype is relatively rare in white populations, in previous studies patients homozygous or heterozygous (TT and TC genotypes, respectively) were combined for analysis.…”
Section: Resultsmentioning
confidence: 91%
“…22 In platelets, aggregation after epinephrine and after the combination of epinephrine and ADP was significantly enhanced in carriers of the 825T allele. 25 Increased G-protein activation is not only observed in vitro 3 but also in cells studied ex vivo. 22,25 Baumgart et al 23 have shown in vivo an increased constriction of coronary arteries after a bolus intravenous injection of an ␣ 2 -adrenoceptor-activating compound in 825T allele carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, alternative ways the C825T polymorphism could influence incidence of or mortality in MI: Dobrev et al [24] have shown altered cardiac potassium currents in homozygous carriers of the T allele, an observation that gives reason to speculate whether carriers of the 825T allele might be more prone to malignant arrythmia, a commonly lethal complication in myocardial infarctions. Also the recently observed enhanced epinephrine-induced platelet aggregation in individuals with the 825T allele [25] could very well be a contributing factor to the death from MI. Finally an increased vasoconstriction was recently observed [26] in carriers of the T-allele.…”
Section: Discussionmentioning
confidence: 97%
“…1 In this context it is of importance, that genetic variants were also shown to alter aggregation, as in platelets obtained from carriers of the G␤3 825T allele, the slopes and maximum of secondary aggregation were significantly enhanced after epinephrine challenge. 37 This phenomenon appeared independent of platelet secretion or inhibition of the adenylylcyclase and may suggest that this enhanced reactivity might also increase platelet reactivity in vivo.…”
Section: Combined Analysismentioning
confidence: 91%